2022
DOI: 10.1227/ons.0000000000000531
|View full text |Cite
|
Sign up to set email alerts
|

Novel Merging of CT and MRI to Allow for Safe Navigation into Kambin's Triangle for Percutaneous Lumbar Interbody Fusion—Initial Case Series Investigating Safety and Efficacy

Abstract: BACKGROUND: For percutaneous lumbar fusion (percLIF), magnetic resonance imaging and computed tomography are critical to defining surgical corridors. Currently, these scans are performed separately, and surgeons then use fluoroscopy or neuromonitoring to guide instruments through Kambin's triangle. However, anatomic variations and intraoperative positional changes are possible, meaning that safely accessing Kambin's triangle remains a challenge because nerveroot visualization without endoscopes has not been th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…51 However, they also reported that the rail-road technique of placing a tapered dilator followed by a snugly fitting cannula does not increase the frequency of ENR injury as previously thought in the literature. 52,53 Additionally, the authors mentioned that ENR visualization was often difficult given that the nerve was not always a perfect oval shape. Without accurately visualizing the nerve root, truly measuring the maximum safe area of Kambin's bony triangle is limited.…”
Section: Discussionmentioning
confidence: 99%
“…51 However, they also reported that the rail-road technique of placing a tapered dilator followed by a snugly fitting cannula does not increase the frequency of ENR injury as previously thought in the literature. 52,53 Additionally, the authors mentioned that ENR visualization was often difficult given that the nerve was not always a perfect oval shape. Without accurately visualizing the nerve root, truly measuring the maximum safe area of Kambin's bony triangle is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the insertion of these devices requires less nerve root retraction and potentially reduces postoperative complications such as cage subsidence [21]. Similarly, the MIS-TLIF platform has become a cornerstone for integrating cutting-edge imaging technologies such as robotic assistance, 3D neurosegmentation, and augmented reality [24][25][26]. These advancements have solidified the role of the MIS-TLIF as a fundamental framework for ongoing research and development in spine surgery.…”
Section: Minimally Invasive Transforaminal Lumbar Interbody Fusionmentioning
confidence: 99%
“…(3) identifying potential anatomic anomalies like conjoined nerve roots; and (4) comparing the areas of each safe corridor to reduce the risk of iatrogenic injury. Tabarestani et al showcased the first practical application of this technology in a small case series where Kambin's Triangle volumes were measured for all patients bilaterally at the level of operation [26]. By comparing contralateral areas, the surgeon was able to decide on the 'ideal' laterality of their approach, entering the largest, safest triangle with the greatest distance from the exiting nerve root.…”
Section: Three-dimensional Neurosegmentationmentioning
confidence: 99%
See 2 more Smart Citations